2016
DOI: 10.5603/gp.2016.0055
|View full text |Cite
|
Sign up to set email alerts
|

The application of CYFRA21-1 in cervical lesions screening in high-risk human papillomavirus infected women

Abstract: Objectives: To investigate the role of cytokeratin-19 fragment (CYFRA21-1) in cervical lesions screening in high-risk human papillomavirus (HR-HPV) infected women. Material and methods:The study was a retrospective study. First, the results of CYFRA21-1, cytology (TCT), and HR-HPV examinations of 1039 outpatients from gynecology department in Tumor Hospital Affiliated to Xinjiang Medical University were collected. Then, the data was analyzed using a series of statistical methods. Results:There was a correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Cervical cancer was one of the most common malignant tumors in China, in which its prevalence rate was 7th in all cancers and its mortality was 8th in all female cancers [1]. HPV infection is known as the main cause of cervical cancer; most of HPV infection could be cleaned by the host immune responses, but some persistent HPV infection would lead to the cytopathy of cervical cancer cells [2][3][4]. The previous studies found that the HPV persistent infection consisted of two phases: in the first phase of viral replication, HPV firstly infected basal cells of the cervix, bare virus DNA was the free state in the host cell nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer was one of the most common malignant tumors in China, in which its prevalence rate was 7th in all cancers and its mortality was 8th in all female cancers [1]. HPV infection is known as the main cause of cervical cancer; most of HPV infection could be cleaned by the host immune responses, but some persistent HPV infection would lead to the cytopathy of cervical cancer cells [2][3][4]. The previous studies found that the HPV persistent infection consisted of two phases: in the first phase of viral replication, HPV firstly infected basal cells of the cervix, bare virus DNA was the free state in the host cell nucleus.…”
Section: Introductionmentioning
confidence: 99%